The Importance of Transparency in Tax Reporting and Its Role in Improving the Reputation of Companies: An Applied Study at the Iraqi Public Tax Authority for the Period 2018–2024 - Arshed Rashed; Mohammed Ali; Iqbal Abed (Indonesian Journal Publisher, 2026)
It aims Search to study importance Transparency in Report tax and its role in to improve reputation Companies, with the focus on an experience Authority public For taxes Iraqi For the period 2018-2024. It stems importance Search from The role pivotal For transparency tax in Strengthening trust investors and customers and the public In companies, Please on to support credibility Authority public For taxes As an entity Organizational. Adopted. Search on Curriculum Descriptive Analytical, where It was completed collection Data from during Surveys Directed For companies The Great And the average, Interviews with Officials Taxes, In addition to analysis Reports tax Annual Issued on Authority public For taxes . Also It was completed Use Methods Analysis statistician To determine relationship between level Transparency in Report tax and reputation companies in market Iraqi. It showed Results that there relationship Positive clear between Commitment With transparency tax and improving reputation Institutional For companies, where It turned out that companies that Track practices tax transparent Enjoy With credibility higher, And less In it Risks Legal, And it increases level satisfaction Customers and investors About it . As well . between Search that Strengthening Programs Awareness Taxation, and development Organized Regulatory Effective, and encouragement Disclosure The complete and flour on Obligations Taxation, Contributes In a way direct in building reputation institutional strong and investigation Compliance tax Sustainable . And concludes Search to that Transparency in Report tax Not merely commitment legal, but rather tool strategy To promote trust and improving image companies The Authority public For taxes on end whether, He is what Enhances the environment investment And contributes in development Economy National.